The The Effect of Mask Use in Maximum Physical Activity Toward Leukocyte Total - Mandosir, Yohanis Manfred (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
The use of masks has to do for everyone who does activities outside the home. This applies when people perform physical activities outside the home. The study aims to determine the effect of using a mask on the leukocytes total when doing physical activity running. The research method used an experiment with a randomized pretest-posttest comparison group design. There are 5 participants. Data were collected through a running test. The data analysis technique used Paired Sample T-test and Independent T-test. The results of the paired t-test concluded that there was a significant effect (0.03 < 0.05) on the number of leukocytes between before and after doing a maximum activity without a mask. Meanwhile, participants who wore masks did not show any difference in the number of leukocytes before and after maximum physical activity (0.13 > 0.05). The results of the independent t-test concluded that there was no difference in the number of leukocytes before and after maximum activity without a mask with wearing a mask. The results of the study have implications for understanding various physical activities in increasing the number of leukocytes, but the use of masks does not affect maximum physical activity.